2013
DOI: 10.1007/s12262-013-0873-9
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Technique of Trocar Fixation During Pediatric Laparoscopy with Foley Catheter Sleeve

Abstract: We describe a simple method of fixing trocars to the abdominal wall in infants and children using small pieces of 16-or 18-Fr Foley catheter as a sleeve over the trocar. The sleeve holds the trocar snugly and is fixed to the skin with silk stitch. This technique is simple, quick, efficacious, and inexpensive, and it does not require any special equipment and can be used with any trocar size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Yip et al reported using an adhesive attached to the trocar and a silk stitch anchored to neighboring skin , Millán et al used sterile nylon plastic seal wrapped around the trocar and a 2‐0 silk thread tied around the plastic seal . Others have reported using small pieces of Foley catheter as a sleeve , special devices , as well as many other techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Yip et al reported using an adhesive attached to the trocar and a silk stitch anchored to neighboring skin , Millán et al used sterile nylon plastic seal wrapped around the trocar and a 2‐0 silk thread tied around the plastic seal . Others have reported using small pieces of Foley catheter as a sleeve , special devices , as well as many other techniques.…”
Section: Discussionmentioning
confidence: 99%